Roles of caudal-related homeobox gene Cdx1 in oesophageal epithelial cells in Barrett's epithelium development. Issue 5 (9th January 2009) - Kazumori, H; Ishihara, S; Kinoshita, Y
Abstract : Background and aims: The mechanism of transformation to intestinal metaplasia in Barrett's oesophagus has not been clarified. We previously reported that bile acids activate the Cdx2 promoter via nuclear factor kappa B (NF-κB) and stimulate production of Cdx2 protein in oesophageal keratinocytes with a resulting production of intestinal type mucin. In addition to Cdx2, Cdx1 may play an important role in the development of Barrett's oesophagus. Therefore, we studied the direct effects of bile acids on the expression of Cdx1 as well as the precise mechanisms of Cdx1 expression in cultured oesophageal squamous epithelial cells. Furthermore, we investigated the relationship between Cdx1 and Cdx2 expression in cultured oesophageal squamous epithelial cells. Methods: A rat model of Barrett's oesophagus was produced by anastomosing the oesophagus and jejunum. The expression of Cdx1 was investigated by immunohistochemistry, while the response of that expression to bile acids was studied using a Cdx1 promoter luciferase assay. In addition, oesophageal squamous epithelial cells were transfected with a Cdx1 or Cdx2 expression vector, after which their possible transformation to intestinal-type epithelial cells was investigated. Results: In our Barrett's rat model, the metaplastic epithelium and adjoining squamous epithelium strongly expressed Cdx1. Further, the bile acids mixture dose-dependently increased Cdx1 promoter activity and Cdx1 protein in oesophageal epithelial cells. Transfection of the Cdx1 expression vector in cultured oesophageal epithelial cells induced production of Cdx2 protein. Conclusion: Bile acid-induced sequential expression of Cdx1 followed by Cdx2 may have an important role in the development of Barrett's epithelium.